Mantle Dynamics of the Long‐Lived Middle Yangtze Basaltic Field: Insight From a Combined Geochemical and Numerical Modeling Approach - Hong‐Kun Dai; Qing Xiong; Jian‐Ping Zheng (Geochemistry, Geophysics, Geosystems)
Abstract Melting for the generation of intracontinental diffuse basaltic fields is generally ascribed to the effects from lithospheric dynamic processes, but how the asthenospheric dynamics influence the overlying lithosphere remains poorly known. Here, this is explored via a combined geochemical and numerical modeling study on the long‐lived Middle Yangtze basaltic field adjacent to the Dabie orogenic belt, central China. This basaltic field with a southwestard younging trend consists of 110–40 Ma basaltic rocks that show alkaline to sub‐alkaline major‐oxide compositions, oceanic island basalt‐like trace‐element patterns and MORB‐like Sr‐Nd‐Pb isotopic ratios. The elemental and isotopic signatures show that the basaltic episodes generally underwent fractionation in the crust‐mantle transition zone from sub‐alkaline parental melts, which were produced by decompression melting of asthenosphere under a thinned (<2 GPa) lithosphere. Thermodynamic‐based Bayesian probabilistic inversions on rare‐earth element data further show that the melting for different basaltic episodes occurred at consistently shallow depths (40–60 km) and ambient mantle‐like potential temperatures (1350–1400°C). Together with regional lithospheric seismic imaging and the orogenic evolution nearby, the southwestard younging trend likely records progressive erosion of the basal lithosphere from the northern margin of the Yangtze block to its interior; the lithospheric thinning was likely triggered by an inland propagating chain of mantle instabilities at lithosphere‐asthenosphere boundary initiated by the delamination of the Dabie orogenic root. We suggest that the proposed model should have general relevance to many other intraplate diffuse basaltic fields with similar spatiotemporal features.